2015
DOI: 10.17645/si.v3i3.139
|View full text |Cite
|
Sign up to set email alerts
|

Intersectoral Action to Enhance the Social Inclusion of Socially Vulnerable Youth through Sport: An Exploration of the Elements of Successful Partnerships between Youth Work Organisations and Local Sports Clubs

Abstract: Research shows that participation in sport is positively related to self-esteem, self-regulation skills, and social inclusion. As socially vulnerable youngsters participate less frequently in sports activities than their average peers, youth work organisations try to guide their clients (i.e., socially vulnerable youngsters) to local sports clubs and inclusive sports activities. Inclusive sports activities, however, cannot be provided by youth work organisations alone. Therefore, in the Netherlands, intersecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
9
1
Order By: Relevance
“…For example, Harris et al (2009) found that governmental expectations often do not suit sports clubs' interests, and that many sports clubs lack the physical, financial and human resources to meet these expectations. Despite these criticisms, the present study as well as previous research (Hermens et al 2015) show that some sports clubs aspire to serve as a youth development setting for socially vulnerable youths. Therefore, we recommend that local governments find out which sports clubs have such ambitions, link youth-care to these clubs and support information exchange between both organisations.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…For example, Harris et al (2009) found that governmental expectations often do not suit sports clubs' interests, and that many sports clubs lack the physical, financial and human resources to meet these expectations. Despite these criticisms, the present study as well as previous research (Hermens et al 2015) show that some sports clubs aspire to serve as a youth development setting for socially vulnerable youths. Therefore, we recommend that local governments find out which sports clubs have such ambitions, link youth-care to these clubs and support information exchange between both organisations.…”
Section: Discussioncontrasting
confidence: 59%
“…Despite these criticisms, the present study as well as previous research (Hermens et al . ) show that some sports clubs aspire to serve as a youth development setting for socially vulnerable youths. Therefore, we recommend that local governments find out which sports clubs have such ambitions, link youth‐care to these clubs and support information exchange between both organisations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scenarios described different types of youths and addressed various types of problem behaviour that are often prevalent in youth care settings. The scenarios were based on interviews conducted with youth care professionals, where they described the issues and behaviour of socially vulnerable youth (Hermens, Super, Verkooijen, & Koelen, 2015). In preparation for the interviews, the main investigator (SS) conducted two pilot interviews to ensure that the interview questions were comprehensible and that the scenarios were understandable for the interviewees.…”
Section: Interview Guidementioning
confidence: 99%
“…As the care sport connector is new as well its area of inquiry and action, conceptual clarification is demanded [9]. The Healthy Alliances (HALL) framework seems to be a useful framework to study the factors that hinder or facilitate the success of intersectoral collaboration and has been successfully used to study intersectoral collaboration initiated by care sport connectors [10] and by youth-care organisations [11], amongst others. The HALL framework identifies three clusters of factors.…”
mentioning
confidence: 99%